2020
DOI: 10.7326/m20-3689
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of COVID-19 in HIV-Positive Persons Receiving Antiretroviral Therapy

Abstract: This study describes the incidence and severity of COVID-19 among 77 590 HIV-positive patients receiving antiretroviral therapy (ART). These findings warrant further investigation of HIV ART in HIV preexposure prophylaxis studies and randomized trials among persons without HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
316
4
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(348 citation statements)
references
References 51 publications
23
316
4
5
Order By: Relevance
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIV-positive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 89%
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIV-positive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 89%
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIVpositive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 89%
“…Another difference between the two Spanish cohorts lies in the prior antiretroviral treatment for HIV. The antiviral activity of lopinavir / ritonavir described against MERS or SARS [37] , as well as the recently demonstrated efficacy of remdesivir [13] (a nuclotide analog that has similarities to tenofovir), have suggested that patients with HIV infection, on antiretroviral therapy with protease inhibitors or tenofovir (TDF), may have a lower infection rate or severity [38] . No conclusions can be drawn with our data in this regard.…”
Section: Discussionmentioning
confidence: 99%